2002
DOI: 10.1017/s0033291702006190
|View full text |Cite
|
Sign up to set email alerts
|

Lower prevalence of pre-morbid neurological illness in African-Caribbean than White psychotic patients in England

Abstract: African-Caribbean patients with psychosis have experienced less pre-morbid neurological illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
(29 reference statements)
0
11
0
1
Order By: Relevance
“…The migration effect is not due to higher rates in the émigrés' country of origin. [9][10][11] This, along with the finding that lifetime morbidity risks for parents of black Caribbean and white subjects with schizophrenia are similar 42 and the lack of neurodevelopment markers in black Caribbean people who develop schizophrenia, 43 has been the main evidence against a predominantly genetic explanation of increased incidence.…”
Section: Meaning Of the Findingsmentioning
confidence: 99%
“…The migration effect is not due to higher rates in the émigrés' country of origin. [9][10][11] This, along with the finding that lifetime morbidity risks for parents of black Caribbean and white subjects with schizophrenia are similar 42 and the lack of neurodevelopment markers in black Caribbean people who develop schizophrenia, 43 has been the main evidence against a predominantly genetic explanation of increased incidence.…”
Section: Meaning Of the Findingsmentioning
confidence: 99%
“…More speculatively, it has been proposed that cephalopelvic disproportion arising from improved nutritional standards could lead to an elevated incidence of schizophrenia among second-generation migrants (64). Two studies have investigated history of obstetric complications in African Caribbean versus white British-born patients (65,66). Both studies found fewer obstetric complications in African Caribbean patients, and no differences in first-versus second-generation African Caribbean patients (65).…”
Section: How Well Do Current Hypotheses Concerning Migrants Fit the Dmentioning
confidence: 99%
“…African Caribbeans are approximately 40% less likely to suffer from a continuous illness than British whites, 46 and it is suggested that they are less likely to have a history of obstetric complications or neurological illness premorbidly. 47 It has been hypothesized that the good symptomatic prognosis reflects increased rates of illness in less neurologically and genetically vulnerable people who have had relatively normal early development but have been exposed to social stressors that have promoted psychosis. One possible contributing factor is racial dis-crimination.…”
Section: Issues Concerning Ethnicitymentioning
confidence: 99%